Satisfaction with amplification in daily life (SADL) in different types and degrees of hearing loss - Abdul Ghani, Nursakinah; Wan Ahmad, Wan Aslynn Salwani (IIUM Press, 2018)
Introduction: The aim of this study is to determine the satisfaction level of hearing aids users in different types and degrees of hearing loss using the satisfaction with amplification in daily life (SADL) questionnaire.